IMPACT OF BARIATRIC SURGERY IN ANXIETY AND ORAL CONDITION OF OBESE INDIVIDUALS: A COHORT PROSPECTIVE STUDY - TINÓS,Adriana Maria Fuzer Grael (2021)
ABSTRACT Background: Obesity and bariatric surgery may be related with mental and oral disorders. Aim: To evaluate the impact of bariatric surgery on anxiety, initial dental caries lesion and gingival bleeding in obese patients. Methods: Eighty-nine patients were divided in two groups: Control Group (CG) - obese patients and Experimental Group (EG) - patients submitted to bariatric surgery. EG was analyzed before and 12 months after bariatric surgery; for the CG, was respected an interval of 12 months between the evaluations. International Caries Detection and Assessment System, Gingival Bleeding Index and Trace-State Anxiety Inventory were used. Medical profile, anthropometrics data, sociodemographic and behavioral variables were considered. Results: There were no statistically significant differences between groups in evaluation times regarding to initial dental caries lesion and anxiety. However, the number of teeth with initial dental caries lesion (p=0.0033) and gingival bleeding (p<0.0001) increased significantly after bariatric surgery in EG. Conclusion: These results reinforce the need for multi-professional team follow-up, including dental care, for both obese and bariatric patients.